Contrasted photochromic and luminescent properties in dinuclear Pt(ii) complexes linked through a central dithienylethene unit. Issue 63 (18th July 2016) - Boixel, Julien; Zhu, Yifan; Le Bozec, Hubert; Benmensour, Mohamed Ali; Boucekkine, Abdou; Wong, Keith Man-Chung; Colombo, Alessia; Roberto, Dominique; Guerchais, Véronique; Jacquemin, Denis
Abstract : Two unprecedented photochromic complexes, Pt-A andPt-B, have been characterised. Abstract : We disclose two unprecedented complexes built with a central dithienylethene photochrome connecting two cyclometalated Pt(ii ) moieties either on the reactive carbon atoms or on the lateral non-reactive carbon atoms of the photochrome. The two systems show vastly different properties that are rationalised thanks to quantum-chemical calculations.